Estimating the electron energy and the strength of the electric field within sprites using ground-based optical data observed over South African storms. (15th November 2021) - Nnadih, Stanislaus; Kosch, Michael; Mlynarczyk, Janusz
Abstract: We present a new simplified method to estimate the characteristic electron energy and electric field within a mesospheric transient luminous event using ground-based calibrated and filtered optical data. We assume non-relativistic motion, a Maxwell-Boltzmann distribution, a model of the electron-neutral collision frequency, elastic electron collisions, that the collisional excitation cross-section can be assigned to a single value, and that each electron-neutral collision produces one photon on average. Example observations of carrot sprites over South Africa give estimated electron energy of 4.6–4.9 ± 0.03 eV, which compares favourably with previous similar results using more sophisticated methods. Ideally, two wavelengths should be observed simultaneously but we show a good estimate is possible with only the bright N2(1 PG) red emission. Highlights: We present a simplified approach to estimate the characteristic electron energy and electric field within sprites events. The estimated values from our ground-based observations were comparable to space-based measurements. The study also shows the strength of the electric field within sprites increases with a decrease in altitude.,